2022
DOI: 10.48550/arxiv.2203.08240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chaotic Dynamics of the Mass Deformed ABJM Model

Abstract: We explore the chaotic dynamics of the mass deformed ABJM model. To do so, we first perform a dimensional reduction of this model from 2 + 1-to 0 + 1dimensions, considering that the fields are spatially uniform. Working in the 't Hooft limit and tracing over ansatz configurations involving fuzzy two spheres, which are described in terms of the GRVV matrices with collective time dependence, we obtain a family of reduced effective Lagrangians and demonstrate that they have chaotic dynamics by computing the assoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Let us also note that, recently, we have also studied the chaotic dynamics emerging from the mass deformed ABJM model using similar methods and found that the Lyapunov exponents vary either 𝜆 𝐿 ∝ (𝐸/𝑁 2 ) 1/3 or 𝜆 𝐿 ∝ (𝐸/𝑁 2 − 𝛾 𝑁 ) 1/3 , where 𝛾 𝑁 (𝑘, 𝜇) is a constant determined in terms of the parameters of this model. Our results, including the critical temperature in regard to the MSS bound are presented in the article [42].…”
Section: Discussionmentioning
confidence: 99%
“…Let us also note that, recently, we have also studied the chaotic dynamics emerging from the mass deformed ABJM model using similar methods and found that the Lyapunov exponents vary either 𝜆 𝐿 ∝ (𝐸/𝑁 2 ) 1/3 or 𝜆 𝐿 ∝ (𝐸/𝑁 2 − 𝛾 𝑁 ) 1/3 , where 𝛾 𝑁 (𝑘, 𝜇) is a constant determined in terms of the parameters of this model. Our results, including the critical temperature in regard to the MSS bound are presented in the article [42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, note that the model (1.3) is very similar to some spatially reduced string and gauge models [93,[99][100][101][102][103][104][105][106][107][108][109]. In particular, the N = 3 variant of (1.3) is nothing but a spatially reduced SU (2) Yang-Mills [99], which is known to possess a nonzero classical Lyapunov exponent κ ∼ 4 √ E, see [93,[100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…4π is no longer level quantized. A more comprehensive discussion on the latter fact may be found in [9].…”
Section: Mass-deformed Abjm Model With Spatially Uniform Fieldsmentioning
confidence: 99%
“…In a more recent paper [9], we have examined chaos emerging from the massive deformation of the Aharony-Bergman-Jafferis-Maldacena (ABJM) model. Here, I will be reporting on a part of this work.…”
Section: Introductionmentioning
confidence: 99%